Fractal Growth of Zinc Dendrites - AKBAR, SHAZIA; IMAM NAQVI, IFTIKHAR; MUHAMMAD, MAHBOOB; ZAHIR, ERUM (Asian Journal of Chemistry, 2010)
An insight into diffusion limited aggregation (DLA) guides the interpretation of cluster designs. The structure and growth pattern of the zinc dendrites are similar to the Witten-Sander DLA model. The fractal dimension of zinc dendrites is 1.669 measured by Box-counting dimension method. This value is quite similar to the two dimensional DLA model (1.666). This fractal analysis suggested that zinc dendrites are two dimensional aggregates , have fractal nature and formed on the basis of DLA model. This study also revealed that zinc dendrites growth pattern is affected by different experimental conditions such as concentration of electrolyte, thickness of electrolyte layer, voltage variation, solvent nature and anion variation.